Effect of alloying on the dynamics of coherent acoustic phonons in bismuth double perovskite single crystals - Lin, Xihong (2021)
The bismuth double perovskite Cs2AgBiBr6 has been regarded as a potential candidate for lead-free perovskite photovoltaics. A detailed study on the coherent acoustic phonon dynamics in the pure, Sb- and Tl-alloyed Cs2AgBiBr6 single crystals is performed to understand the effects of alloying on the phonon dynamics and band edge characteristics. The coherent acoustic phonon frequencies are found independent on the alloying, while the damping rates are highly dependent on the alloying. Based on the mechanism of coherent acoustic phonon damping, a technique has been successfully developed that can accurately extract the absorption spectra near the indirect band gap for these single crystals with coefficients on the order of 10^2 cm^(-1).